2015
DOI: 10.3390/ijms160819713
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Amorphigenin on the Mitochondrial Complex I of Culex pipiens pallens Coquillett (Diptera: Culicidae)

Abstract: Previous studies in our laboratory found that the extract from seeds of Amorpha fruticosa in the Leguminosae family had lethal effects against mosquito larvae, and an insecticidal compound amorphigenin was isolated. In this study, the inhibitory effects of amorphigenin against the mitochondrial complex I of Culex pipiens pallens (Diptera: Culicidae) were investigated and compared with that of rotenone. The results showed that amorphigenin and rotenone can decrease the mitochondrial complex I activity both in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…No comprehensive study has been made of the inhibitory properties of hydroxylated rotenoids against complex I or their ability to selectively target prostate cancer cells, though a number of reports have been made on the cytotoxicity of certain hydroxylated rotenoids. Thus, a library of 29 hydroxylated rotenoids was prepared from rotenone ( 1 ) and deguelin ( 2 ) to identify inhibitors of complex I that might be better suited to development as therapeutics than the parent compounds. The inhibitory effect of each hydroxylated rotenoid on complex I was determined and its hydrophobicity predicted.…”
mentioning
confidence: 99%
“…No comprehensive study has been made of the inhibitory properties of hydroxylated rotenoids against complex I or their ability to selectively target prostate cancer cells, though a number of reports have been made on the cytotoxicity of certain hydroxylated rotenoids. Thus, a library of 29 hydroxylated rotenoids was prepared from rotenone ( 1 ) and deguelin ( 2 ) to identify inhibitors of complex I that might be better suited to development as therapeutics than the parent compounds. The inhibitory effect of each hydroxylated rotenoid on complex I was determined and its hydrophobicity predicted.…”
mentioning
confidence: 99%
“…In another work, the inhibitory action of amorphigenin against the mitochondrial complex I of C. pipiens pallens was studied in comparison to rotenone ( Mingshan et al, 2015 ). It was observed that both compounds abolish mitochondrial complex I activity in vitro and in vivo.…”
Section: Pharmacological Activity Of Amorpha Fruticosa mentioning
confidence: 99%
“…Additionally A. fruticosa is attacked only by several more or less specialized insects (Petrova et al 2012) because the plant contains compounds with insecticide activity (Brett 1946). These compounds are the rotenoids (Moring and McChesney 1979;Berenbaum 1989;Kole et al 1992;Konoshima et al 1993;Fang and Casida 1998;Ivanescu et al 2014;Kariuki et al 2014;Mingshan et al 2015). In fact rotenone is a botanical insecticide, which has been used for centuries and is still used worldwide (Gupta 2007).…”
Section: Introductionmentioning
confidence: 99%